MANAJEMEN MUTU DOSEN - Husainie Usman; Hasbi Sjamsir; AS, Susanto (BEduManagers Journal : Borneo Educational Management and Research Journal, 2020)
The purpose of this research were to know:quality management of lecturer in Caturdharma of Higher Education and find new concept of lecturer qualitymanagement.The study used a qualitative approach with case study type. Data were collected through participantobservation,in-depth interviews,and documentation.The research instrument is the researcher himself.The key person were the Chairman,Vice Chairman, and Stikes lecturer. Data were analyzed using Miles,Huberman,&Saldana model. Validity of data through credibility, transferability, dependability, and confirmability. As the result of this research about the quality management lectures were:(1)learning area is fulfilled if according to planning, implementation and supervision standard;(2)the field of study is determined by eight standards;(3) the field of Community Service is determined by eight standards;(4)the field of Al-Islam and Kemuhammadiyahan is determined by the introduction, appreciation, and practice of the Qur'an,Hadith, and Ra'yu;Amar ma'ruf nahi munkar, and live Muhammadiyah, do not seek livelihood in Muhammadiyah.(5)A new concept of lecturer quality management is nine steps